2020
DOI: 10.1128/msystems.00658-19
|View full text |Cite
|
Sign up to set email alerts
|

Transgenic Testing Does Not Support a Role for Additional Candidate Genes in Wolbachia Male Killing or Cytoplasmic Incompatibility

Abstract: Endosymbiotic bacteria in the genus Wolbachia remarkably infect nearly half of all arthropod species. They spread in part because of manipulations of host sexual reproduction that enhance the maternal transmission of the bacteria, including male killing (death of infected males) and unidirectional cytoplasmic incompatibility (CI; death of offspring from infected fathers and uninfected mothers). Recent discoveries identified several genes in prophage WO of Wolbachia (wmk, cifA, and cifB) that fully or partially… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
31
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(36 citation statements)
references
References 69 publications
4
31
0
Order By: Relevance
“…When wmk was transgenically expressed with the most likely upstream start codon, the phenotype was lost, and no biased sex ratio resulted. We also showed that some non-male-killing strains tended to have more of the alternative start codons, establishing a hypothesis that differences in transcript length could significantly alter phenotype 22 . To determine if w Rec and w Suzi wmk transgene phenotypes are similarly sensitive to transcript changes, we expressed them with upstream codons that are native to each of their genetic sequences.…”
Section: Resultssupporting
confidence: 56%
See 3 more Smart Citations
“…When wmk was transgenically expressed with the most likely upstream start codon, the phenotype was lost, and no biased sex ratio resulted. We also showed that some non-male-killing strains tended to have more of the alternative start codons, establishing a hypothesis that differences in transcript length could significantly alter phenotype 22 . To determine if w Rec and w Suzi wmk transgene phenotypes are similarly sensitive to transcript changes, we expressed them with upstream codons that are native to each of their genetic sequences.…”
Section: Resultssupporting
confidence: 56%
“…Relevant to the work here, we previously provided evidence that transcriptional changes in wmk expression may contribute to differences in male-killing abilities between Wolbachia strains or hosts 22 . For instance, some strains contain alternative start codons upstream of the annotated start for wmk and these upstream regions are expressed in the w Mel strain.…”
Section: Resultssupporting
confidence: 55%
See 2 more Smart Citations
“…It is worth noting that none of the CI-associated genes presented here are among those that were previously shown not to cause CI when transgenically expressed in Wolbachia free D. melanogaster (Perlmutter, et al 2020). It is also important to consider that the potential CIassociated effect of these genes may be indirect rather than a direct role in mod or resc.…”
Section: Are There More Wolbachia Genes Involved In CI Than Cif?mentioning
confidence: 87%